2014
DOI: 10.2217/pgs.14.126
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 5-Fluorouracil Toxicity: DPD Genotype and 5,6-Dihydrouracil: Uracil Ratio

Abstract: These results suggest that the baseline UH2:U plasma ratio in most individuals reflects the nonsaturated state of DPD and is not predictive of decreased DPD activity. It may, however, be highly predictive at increased substrate concentrations, as observed during 5-FU administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 51 publications
2
76
0
Order By: Relevance
“…In contrast to this study is recent work conducted by investigators from Switzerland who found that the baseline UH 2 /U plasma ratio was a relatively poor predictor of reduced DPD activity and associated 5-FU toxicity [81]. This group determined that the UH 2 /U ratio was a reflection of first-order DPD kinetics where the enzyme was not saturated, which then explains their finding of overlap between ratios of carriers of DPD risk variants and non-carriers.…”
Section: Dihydrouracil/uracil Ratio and Uracil Breath Testmentioning
confidence: 65%
“…In contrast to this study is recent work conducted by investigators from Switzerland who found that the baseline UH 2 /U plasma ratio was a relatively poor predictor of reduced DPD activity and associated 5-FU toxicity [81]. This group determined that the UH 2 /U ratio was a reflection of first-order DPD kinetics where the enzyme was not saturated, which then explains their finding of overlap between ratios of carriers of DPD risk variants and non-carriers.…”
Section: Dihydrouracil/uracil Ratio and Uracil Breath Testmentioning
confidence: 65%
“…The c.1129-5923C>G intronic polymorphism (rs75017182) results in aberrant splicing and is likely to be the responsible variant for the effect on DPD enzyme activity [3,14]. The frequency of heterozygous patients in Caucasian populations was reported to vary between 2.6 and 6.3% [14,15,42,49,50]. DPD enzyme activity for c.1236G>A carriers was measured in PBMCs in two studies [14,46].…”
Section: Previous Guidelines and Recommendationsmentioning
confidence: 99%
“…Furthermore we observed two homozygous patients with this variant in our own institute with a relevant DPD enzyme activity left of around 50%, showing that this variant does not result in a completely nonfunctional enzyme (Author's Unpublished Data). In the study of Sistonen et al the ratio between endogenous dihydrouracil (DHU) and uracil (U) was measured in patients carrying the c.1129-5923C>G variant [50]. This ratio can be used as a phenotyping marker for DPD enzyme activity, as described in several studies [51][52][53][54][55].…”
Section: Previous Guidelines and Recommendationsmentioning
confidence: 99%
“…As a result, we could not confirm that the pharmacokinetics of S-1 differed between the high- and low-dose groups, and it might have been affected not only by the initial dose but by other factors, such as catabolic enzyme and renal function. Dihydropyrimidine dehydrogenase and thymidylate synthase are the rate-limiting enzymes that catabolize 5-fluorouracil, and these enzymes were reported to correlate with the effect of S-1 [22,23,24]; however, these enzyme levels were not examined in the current study. Renal function may also affect the deviation of the plasma concentration of S-1.…”
Section: Discussionmentioning
confidence: 93%